Evaluation of citizenship education and values education in the early years of the republic - Sabri Becerikli; Sevda Gülşah Yıldırım (Institute of Advanced Engineering and Science, 2020)
Many governments in history have always wanted to educate their citizens according to their own perceptions. In the early years of the Republic, the administrators of the Republic of Turkey intended to educate citizens concurrent with the republican regime. The present study aims to investigate and reveal what kind of a citizen was desired to be educated in the first years of the Republic. From this point of view, numerous views of the administrators in the first years of the Republic were revealed and the citizenship education courses (Musahabat-ı Ahlakiye and Malumat-ı Vataniye) which were included in the 1924 Primary Schools Program were addressed. In order for the course to be able to be evaluated in terms of aims and citizenship education, a sample book from the textbooks of Musahabat-ı Ahlakiye and Malumat-ı Vataniye, which were taught in fourth and fifth grades in primary schools, was examined. The present study was designed with document analysis method, one of the qualitative research methods.